INCREASING THE RESISTANCE TO CORROSION OF CONCRETE - Teshaboeva Nodira Djuraevna (Лучшие интеллектуальные исследования, 2023)
Abstract: The article presents the results of studying the erosion resistance of concrete structures used in the construction of buildings and structures.